Two de novo UBR1 variants in trans as a cause of Johanson-Blizzard syndrome - Strych, Lukas; Zavoral, Tomas; Komrskova, Pavla; Vanecek, Tomas; Subrt, Ivan (Biomedical papers, 2025)
Aims/Background. Johanson-Blizzard syndrome (JBS) is a rare autosomal recessive disease caused by pathogenic variants in the UBR1 gene. JBS is usually suspected based on characteristic anomalies, but only genetic testing provides a definitive diagnosis. Since most variants are inherited from the parents, we aimed to identify the causal variants in a Czech proband with clinically suspected JBS and perform segregation analysis. Methods. A proband with clinically suspected JBS underwent clinical exome sequencing (CES). Sanger sequencing was used for the validation, characterization, and segregation of variants in the family. The variants were also characterized using quantitative real-time PCR (qPCR) and in silico analysis. Results. Using CES in the proband, we identified two novel causal variants in the UBR1 gene, c.3482A>C and c.3509+6T>C. Although the variants were found in trans, neither was detected in the parents. Sanger sequencing of the cDNA revealed that the novel variant c.3509+6T>C caused activation of the non-canonical GC donor splice site. The inclusion of 70 bp of the intronic sequence generated a frameshift and a premature termination codon leading to nonsense-mediated decay, as detected by qPCR. In silico protein structural analysis showed that the novel missense variant c.3482A>C in the zinc-stabilized domain RING-H2 altered a highly conserved zinc-coordinating histidine by proline. Conclusion. To the best of our knowledge, we report the first molecular confirmation of JBS in the Czech Republic and the first identification of two de novo causal variants in two alleles. Our findings also expand the spectrum of pathogenic variants in the UBR1 gene.
Keywords: Johanson-Blizzard syndrome; UBR1 gene; novel variant; de novo